2009
DOI: 10.1101/gr.086652.108
|View full text |Cite
|
Sign up to set email alerts
|

Constructing genomic maps of positive selection in humans: Where do we go from here?

Abstract: Identifying targets of positive selection in humans has, until recently, been frustratingly slow, relying on the analysis of individual candidate genes. Genomics, however, has provided the necessary resources to systematically interrogate the entire genome for signatures of natural selection. To date, 21 genome-wide scans for recent or ongoing positive selection have been performed in humans. A key challenge is to begin synthesizing these newly constructed maps of positive selection into a coherent narrative o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

10
422
1
7

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 407 publications
(440 citation statements)
references
References 124 publications
(121 reference statements)
10
422
1
7
Order By: Relevance
“…Furthermore, it has been suggested that regions identified in multiple analyses are more likely to be true positives. 6,7 Regions of the genome that are part of ongoing selective sweeps may include loci involved in phenotypic outcomes, including both deleterious and protective variants. Thus, haplotypes across regions with evidence of recent selection are of interest to be compared with association signals in genetic mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, it has been suggested that regions identified in multiple analyses are more likely to be true positives. 6,7 Regions of the genome that are part of ongoing selective sweeps may include loci involved in phenotypic outcomes, including both deleterious and protective variants. Thus, haplotypes across regions with evidence of recent selection are of interest to be compared with association signals in genetic mapping.…”
Section: Introductionmentioning
confidence: 99%
“…Suppose a new population emerges, in which A is assumed to be advantageous over B, then, there should be preferential migration of A into this new niche, resulting in an increased effective migration rate. This idea has been frequently used to scan a genome for evidence of selection, and there are many successful demonstrations of selection (for example Akey, 2009). For this kind of largescale polymorphism data analysis, there are many situations where simple summary statistics are very useful and powerful.…”
mentioning
confidence: 99%
“…This pattern is very common in studies on positive natural selection in humans. For example, only ~14.1% loci were identified in two or more studies with large-scale genome-wide scans of PSGs [13]. In the current study, possibly due to the above stated factors, no significant enrichment for any functional category associated with vision was found among the candidates identified by the F ST test.…”
Section: Positively Selected Genes In Domestic Chickens Compared Withmentioning
confidence: 58%
“…First, the distinct statistics applied to scan the genome for positive selection are based on different signatures of population variation [9]. Another reason might be attributable to a pitfall in the outlier approach, whereby an outlier value in one analysis, falling in the 99th percentile of the empirical distribution, may not be classified as an outlier in another study where it may fall within the 98th percentile of the study's empirical distribution [13]. This pattern is very common in studies on positive natural selection in humans.…”
Section: Positively Selected Genes In Domestic Chickens Compared Withmentioning
confidence: 99%